2013
DOI: 10.1109/tuffc.2013.2756
|View full text |Cite
|
Sign up to set email alerts
|

Analytic solution for N-electrode actuated piezoelectric disk with application to piezoelectric micromachined ultrasonic transducers

Abstract: In this work, the deflection equation of a piezoelectrically-driven micromachined ultrasonic transducer (PMUT) is analytically determined using a Green's function approach. With the Green's function solution technique, the deflection of a circular plate with an arbitrary circular/ring electrode geometry is explicitly solved for axisymmetric vibration modes. For a PMUT with one center electrode covering ≈60% of the plate radius, the Green's function solution compares well with existing piece-wise and energy-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…Some work has begun to address the analytical model gap by focusing on the development of plate theory based electromechanical models [1], [3], [13], [22]- [28]. In [3], [22], explicit analytical equations for effective electromechanical coupling k 2 ef f are defined based on material constants and geometric parameters enabling optimized design for high k 2 ef f .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some work has begun to address the analytical model gap by focusing on the development of plate theory based electromechanical models [1], [3], [13], [22]- [28]. In [3], [22], explicit analytical equations for effective electromechanical coupling k 2 ef f are defined based on material constants and geometric parameters enabling optimized design for high k 2 ef f .…”
Section: Introductionmentioning
confidence: 99%
“…With developed analytical models, electrode size optimization performed for high k 2 ef f and deflection [3], [26], [28], [29] demonstrates the usefulness of analytical approaches for more flexible, straight-forward performance optimization via tailored geometry. In support of some analytical modeling endeavors, finite element models have been successfully implemented [22]- [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The piezoelectric micromachined ultrasonic transducers (PMUTs) also emerge as another possible 2D transducer solution for 3D imaging [47][48][49][50][51]. It combines the piezoelectric material with micromachining techniques, trying to exploit the benefits from both worlds.…”
Section: Ultrasonic Transducersmentioning
confidence: 99%
“…As a technology in its early research phase, it has shown initial success of a 5x5 working array [47]. More works are being done to address problems with this technology, including how to enhance the device bandwidth to generate images with better axial resolution; and how to reduce the intrinsic device parasitic capacitance from the high permittivity of the piezoelectric material [48,49,51].…”
Section: Ultrasonic Transducersmentioning
confidence: 99%